Pedestrian route choice model based on friction forces. (October 2014) - Werberich, Bruno Rocha; Pretto, Carlos Oliva; Cybis, Helena Beatriz Bettella
This paper presents a pedestrian route choice model devised to represent the influence of the impedance generated by other pedestrians on the route choice process. This model is inspired by friction force equations, and considers that pedestrians avoid passing near other pedestrians with high relative velocity. The route choice process is based on a weighting of the impedance generated by pedestrians and the path length. A social force model was used to model pedestrian walking behavior. The model is able to reproduce emergent behavior among agents, allowing the assumption that the friction equations may provide a suitable approach to route choice behavior and can also be used as an indirect measure of pedestrian delay.